Knowledge collaborative incentive based on inter-organizational cooperative innovation of project-based supply chain - Guang-dong Wu (Journal of Industrial Engineering and Management (JIEM), 2013)
Purpose: Within project-based supply chain inter-organizational cooperative innovation, the achievement of project value-adding reflects by factors such as project-based organizational effect level, the relationship between project cooperative innovation objectives etc. The purpose is to provide a reliable reference for the contractor reasonably allocate the effect level and resources between the knowledge input and innovation stage and realize the knowledge collaboration for project-based supply chain. Design/methodology/approach: Based on the assumption of equal cooperation between project-based organizations, from the view of maximizing project value-adding and the relationship of effect cost between knowledge input and innovation stage in consideration, the knowledge collaborative incentive model for project-based supply chain inter-organizational cooperative innovation was established, and solved through the first-order and second-order approach, then the digital simulation and example analysis were presented. Findings: The results show that, the project management enterprise resorted to adjust project knowledge collaboration incentive intensity and implemented knowledge input-innovation coordinative incentive strategy, not only could achieve project value-adding maximization, but also could realize net earnings Pareto improvement between project management enterprise and contractor. Research limitations/implications: To simplify the knowledge flow among project-based organizations, the knowledge flow in the model hypothesis is presented as knowledge input and knowledge innovation stage, thus it may affect the final analysis results. Originality/value: In construction project practice, knowledge is become more and more important to achieve project value-adding. The research can provide a theoretical guideline for the project-based organizations, such as the contractor, the owner, especially how to utilize their core knowledge.
Keywords: 650; project-based supply chain; cooperative innovation; knowledge collaboration